Gesichtswahrung, Statuskämpfe und soziale Grenzziehung. Interaktion im urbanen Vergnügen des frühen 20. Jahrhunderts. - Nathaus, Klaus (Deutsches Institut für Urbanistik, 2019)
Historians of tum-of-the-century Germany have argued that popular entertainment blurred dass distinctions, as it appealed to people [rom different walks oflife. The present artide challenges this interpretation. Firstly, it proposes that commercial culture became a site where members of a new middle dass strove for status. Secondly, it aims to explain why respectable men and women engaged in 'improper' amusements in the first place. Thirdly, it identifies 'slumming' as a practice whereby middle-dass patrons oflower dass entertainment reaffirmed social boundaries. Focusing on interactions in physical spaces, the artide presents an approach weH suited to the study of social distinctions in urban popular entertainment before the era of sound film and radio.
Keywords: Stadtgeschichte; Stadtleben; Vergnügungsstätte; Klassengesellschaft; Stadtkultur; Stadtgesellschaft